1998
DOI: 10.1161/01.hyp.31.2.582
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens Increase Transcription of the Human Endothelial NO Synthase Gene

Abstract: Abstract-Estrogens have been found to reduce the incidence of cardiovascular disease that has been ascribed in part to an increased expression and/or activity of the vasoprotective endothelial NO synthase (NOS III). Some reports have shown that the level of expression of this constitutive enzyme can be upregulated by estrogens. The current study investigates the molecular mechanism of the NOS III upregulation in human endothelial EA.hy 926 cells. Incubation of EA.hy 926 cells with 17␤-estradiol or the more sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(140 citation statements)
references
References 48 publications
6
130
0
4
Order By: Relevance
“…Several studies have demonstrated that oestrogen stimulated the synthesis and release of the vasodilator/antiproliferative factor nitric oxide via both a genomic and non-genomic mechanism acting at the level of nitric oxide synthase (Kim et al, 1999;Kleinert et al, 1998). Secondly, oestrogen increased the synthesis of the potent vasodilator prostacylin via a non-genomic action in endothelial cells (Jun et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that oestrogen stimulated the synthesis and release of the vasodilator/antiproliferative factor nitric oxide via both a genomic and non-genomic mechanism acting at the level of nitric oxide synthase (Kim et al, 1999;Kleinert et al, 1998). Secondly, oestrogen increased the synthesis of the potent vasodilator prostacylin via a non-genomic action in endothelial cells (Jun et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Acting via genomic and non-genomic pathways, oestrogen treatment of endothelial cells stimulated nitric oxide synthase mRNA transcription and enzyme activity, respectively (Kim et al, 1999;Kleinert et al, 1998). Nitric oxide is a potent vasodilator of the underlying vasculature, and an important antiproliferative factor (Lloyd-Jones & Bloch, 1996;Garg & Hassid, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…endothelium-dependent genomic action of estrogen in the coronary vasculature Activation of estrogen receptors (ER) mediates the upregulation of eNOS 128,132 via a specific estrogen response element in the eNOS gene promoter region (Figure 2). 133 Muller-Delp and colleagues demonstrated that estrogen treatment increased eNOS protein in coronary arteries of ovariectomized ER α -deficient mice.…”
Section: Dovepressmentioning
confidence: 99%
“…Inhibition by L-NAME, a specific inhibitor of NOSIII, and the fact that NOSII is not expressed under these circumstances, indicate that the most likely candidate for this effect is NOSIII. Indeed it has previously been shown that E2 induces NOSIII expression 21 and activity. 34 Several studies have shown a positive correlation of NOSIII and oestrogen receptors in breast tumours 35,36 and that the low level of NO produced by NOSIII is associated with endothelial proliferation.…”
Section: Discussionmentioning
confidence: 95%